Pembiasaan Akhlak Terpuji pada Anak Tunagrahita di SMPLB Kanigoro Kras Kediri - Khoulita, Ikhfi (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2014)
This study will examine how moral habituation in children with some intellectualimpediments takes place. The location of the study is SMPLB Kanigoro, Kras,Kediri. This study uses a qualitative research method by using interviews,observation and documentation. The results show that the method (habituation)could be a means of forming moral habit for children with limited intelligencedevelopment. With these characteristics, the education provided must adapt to thesituation of children with some intellectual impediment.